Introducing Hair Transplantation into a Facial Plastic Surgery Practice - Bared, Anthony (Facial Plastic Surgery, 2018)
Hair restoration can be an integral addition to the facial plastic surgery practice. As surgeons dedicated to reconstructive and aesthetic surgery of the head and neck, hair restoration is a natural complement to a facial plastic surgeon's practice. This article presents the keys to adding and starting hair restoration to one's facial plastic surgery practice.
Keywords: hair restoration; follicular unit extraction; donor hair harvesting; recipient site creation